The Potential of Brantas River Iron Sand as A Source of Silica and Calsite Materials - Ah. Sulhan Fauzi; Yasinta Sindy Pramesti (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2018)
Brantas River is the second longest river in Java after Bengawan Solo, flowing from Malang, Blitar, Tulungagung, Kediri, Jombang and Mojokerto. In Mojokerto Regency, the river become two branches, the Mas River (towards Surabaya) and the Porong River (towards Porong, Sidoarjo Regency). Brantas has a watershed area (DAS) covering an area of 11,800 km2 or ¼ from the area of East Java Province. The length of the main river 320 km flows around a still active volcano, Mount Kelud. The extent of the Brantas watershed certainly has the abundant potential of iron sand. But the use of Brantas river sand is still limited as a building materials. Even though there are so many ingredients of iron sand such as silica and calsite that can be used for the benefit of others. This research aims to find or identify the content of oxide elements found in iron sand from the Brantas river. The samples of iron sand extracted using permanent magnets were then identified through XRD and SEM tests. XRD results show the content of Calcium Aluminum Silicate (Al2CaO8Si2), magnetite (Fe3O4), Magnesium Vanadium Oxide (Mg0,966 (V1,64Mg0,36) Mg0,105O4) and Sodium Zinc Iron Phosphorus Oxide (Na (Zn0,8Fe0,2) PO4).